1999
DOI: 10.1002/(sici)1521-4095(199903)11:5<408::aid-adma408>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Polymer-Silica Colloidal Nanocomposites via Free-Radical Polymerization of Vinyl Monomers

Abstract: stead of the calculated one [21]. This is due to the fact that, at the self-consistent field level, the excitation energy is overestimated by a factor of 2±3 (this is brought about by the neglect of coulomb and exchange integrals).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 206 publications
(50 citation statements)
references
References 7 publications
(7 reference statements)
1
43
0
1
Order By: Relevance
“…Hence, the silica-polymer nanocomposite particles with various morphologies, such as silica (core)-organic material (shell) [20], organic (core)-silica (shell) [21], raspberry-like [22], snowman-like [23], daisy-shaped, multipod-like [24] and raisin bun-like [25], have been produced by different techniques. These nanocomposite particles are commonly produced by incorporation of colloidal silica in heterogeneous polymerizations, such as emulsion, dispersion and suspension [26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the silica-polymer nanocomposite particles with various morphologies, such as silica (core)-organic material (shell) [20], organic (core)-silica (shell) [21], raspberry-like [22], snowman-like [23], daisy-shaped, multipod-like [24] and raisin bun-like [25], have been produced by different techniques. These nanocomposite particles are commonly produced by incorporation of colloidal silica in heterogeneous polymerizations, such as emulsion, dispersion and suspension [26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…10 It has been widely reported that in situ (co)polymerization of various vinyl monomers in the presence of ultrafine silica sols either in aqueous solution, in alcohol/water mixtures [32][33][34][35][36] or in purely alcoholic media [37][38][39][40] can result in the formation of vinyl polymer/silica nanocomposite particles. For example, Barthet et al 15 described the free radical (co)polymerization of 4-vinylpyridine (4VP) using ammonium persulfate in the presence of an ultrafine silica sol. The resulting colloidal nanocomposite particles had mean diameters of 150 to 170 nm and silica contents as high as 37 % by mass.…”
Section: Introductionmentioning
confidence: 99%
“…One emerging fabrication route makes use of the assembly of colloidal building blocks to construct a more complex nanocomposite supracolloidal structure. The assembly process can be driven or guided by electrostatic forces, such as in heterocoagulation to prepare silica/polymer nanocomposite nanoparticles 8 .…”
Section: Introductionmentioning
confidence: 99%